2022
DOI: 10.1021/acs.est.1c08345
|View full text |Cite
|
Sign up to set email alerts
|

Tools for Understanding and Predicting the Affinity of Per- and Polyfluoroalkyl Substances for Anion-Exchange Sorbents

Abstract: Anion-exchange (AE) sorbents are gaining in popularity for the remediation of anionic per- and polyfluoroalkyl substances (PFAS) in water. However, it is unclear how hydrophobic and electrostatic interactions contribute to anionic PFAS retention. The goal of this study was to understand the effects of PFAS chain length and head group on electrostatic interactions between PFAS and an aminopropyl AE phase. Liquid chromatography–mass spectrometry (LC–MS) was used with an aminopropyl AE guard column to find relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This may allow for the charge(s) on their head groups to be stronger and less delocalized compared to the negative charge on anionic PFAS, thus increasing their capacity to interact with charged soil components. This hypothesis is supported by Parker et al who observed that anionic PFAS with −CH 2 – spacers between the fluorinated tail and the charged head group (e.g., a polyfluorinated fluorotelomer sulfonate) had an overall more negative electrostatic charge than those without the −CH 2 – spacer. A second possibility is that the nonfluorinated aliphatic head groups which, in contrast to the highly lipophobic fluorocarbon chain, should impart some capacity to engage in van der Waals-type interactions with hydrophobic soil components.…”
Section: Resultsmentioning
confidence: 69%
“…This may allow for the charge(s) on their head groups to be stronger and less delocalized compared to the negative charge on anionic PFAS, thus increasing their capacity to interact with charged soil components. This hypothesis is supported by Parker et al who observed that anionic PFAS with −CH 2 – spacers between the fluorinated tail and the charged head group (e.g., a polyfluorinated fluorotelomer sulfonate) had an overall more negative electrostatic charge than those without the −CH 2 – spacer. A second possibility is that the nonfluorinated aliphatic head groups which, in contrast to the highly lipophobic fluorocarbon chain, should impart some capacity to engage in van der Waals-type interactions with hydrophobic soil components.…”
Section: Resultsmentioning
confidence: 69%
“…ERα and ERβ were the most specific of the nuclear receptors, binding only 30–32% of the total UCMR1–4 organic pollutants (Figure ), respectively. This may be attributed to the presence of anionic glutamate (E353 in ERα and E305 in ERβ) in the ligand-binding domain, creating charge repulsion with carboxylates, sulfonates, and chemicals with a negative electrostatic surface potential (PFAS). , Active residues in the remaining Superfamily I class of receptors (MR, AR, GR, PR) included cationic arginine and lysine (R752 of AR; R611 and K667 of GR; R817 of MR; R766 of PR) along with mostly polar amino acids, allowing for polar/anionic pollutants (carboxylates and sulfonates) to interact. Of the proteins in Superfamily II, LXR was the most specific, binding to only 39% of the UCMR organic pollutants, while TRα and TRβ bound to the greatest number.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the detection and remediation of PFAS in the environment have been subjects of significant research and technological advancement [ [128] , [129] , [130] , [131] ]. Parker et al [ 132 ] studied how chain length and head group of PFAS affect their electrostatic interactions with anion-exchange (AE) sorbents, using liquid chromatography-mass spectrometry and calculating average electrostatic potential to predict these interactions, and determining the varying affinity of different PFAS types for AE resins in water treatment scenarios. Sophisticated analytical methods have been developed for PFAS detection, including liquid chromatography-tandem mass spectrometry (LC-MS/MS), which allows for the sensitive and specific identification of individual PFAS compounds even at low concentrations in various matrices [ 133 ].…”
Section: Advances In Detection and Remediationmentioning
confidence: 99%